Sistem Informasi Penjualan Ayam Potong Berbasis Android Pada UD. Abdul Aziz - A Aswan; Budiawan Sulaeman; Rinto Suppa (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2022)
Sales of chicken pieces At “UD. Abdul Aziz" is one of the business entities engaged in sales or referred to as self-employed, sales serving customers, especially in the service sector, still use the manual method. This goods sales information system is made using PHP, HTML and MYSQL. This program allows admins to input data, edit reports, delete data, search transactions. The data inputted are chicken data, chicken type data and chicken sales data. This chicken sales information system can be a solution that can be used to facilitate sales in processing chicken sales data, making it easier, faster and more efficient.